1981
DOI: 10.1002/art.1780240508
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic fasciitis

Abstract: Two patients with clinical and pathologic features of eosinophilic fasciitis manifested serologic and systemic abnormalities that raised the question of the fundamental nature and relationship of eosinophilic fasciitis to scleroderma. In addition to the characteristic features of eosinophilic fasciitis, both patients exhibited arthritis, a predominantly mononuclear cell infiltration of muscles with normal serum muscle enzyme levels, weakly positive serum antinuclear factor, IgA deficiency, and abnormalities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…EF is a scleroderma-like disease characterized by swelling and edematous extremities, hypergammaglobulinemia, and thickened and fibrotic fascia with the infiltration of inflammatory cells, lymphocytes, plasma cells, histiocytes, and eosinophils (6). Although the pathogenesis of EF is not clear, EF is also improved by immunosuppressive treatments, such as corticosteroids and methotrexate (7), suggesting that it is an autoimmune disorder (6,8). Similar to AIH, EF is also known to be complicated by other autoimmune diseases, such as localized scleroderma, autoimmune thyroiditis, systemic lupus erythematosus, and rheumatoid arthritis (9-11).…”
Section: Discussionmentioning
confidence: 99%
“…EF is a scleroderma-like disease characterized by swelling and edematous extremities, hypergammaglobulinemia, and thickened and fibrotic fascia with the infiltration of inflammatory cells, lymphocytes, plasma cells, histiocytes, and eosinophils (6). Although the pathogenesis of EF is not clear, EF is also improved by immunosuppressive treatments, such as corticosteroids and methotrexate (7), suggesting that it is an autoimmune disorder (6,8). Similar to AIH, EF is also known to be complicated by other autoimmune diseases, such as localized scleroderma, autoimmune thyroiditis, systemic lupus erythematosus, and rheumatoid arthritis (9-11).…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies have shown a higher rate of complete response with combination therapy of corticosteroids and methotrexate (7,16,17,19). Other steroid-sparing agents utilized include anti-tumor necrosis factor agents, azathioprine, cyclosporine, imatinib, IVIG, hydroxychloroquine, mycophenolate mofetil, rituximab, sirolimus, and tocilizumab in retrospective cases or case series (10,12,15,17,(20)(21)(22)(23)(24). Given its rarity, treatment from juvenile EF is adapted from treatment for juvenile LS and dermatomyositis (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 7 This led researchers to deal with EF as an autoimmune disease, especially with its coexistence with other auto-immune diseases such as autoimmune thyroiditis 8 and response to corticosteroids. 9 , 10 …”
Section: Review Of Literaturementioning
confidence: 99%
“…Patients presenting with EF are mostly ANA negative in contrast to scleroderma. 10 Scleroderma is mainly a vasculopathy occurring in the capillaries which explains the visceral involvement while in EF, extracutaneous manifestation and Raynaud phenomenon are typically uncommon. 15 However, there are reported cases of interstitial lung disease, 16 pleuropericarditis, 17 and renal disease.…”
Section: Review Of Literaturementioning
confidence: 99%